Significant change of cytochrome P450s activities in patients with hepatocellular carcinoma - Zhou, Jun; Wen, Qiang; Li, Sai-Fei; Zhang, Yun-Fei; Gao, Na; Tian, Xin; Fang, Yan; Gao, Jie; Cui, Ming-Zhu; He, Xiao-Pei; Jia, Lin-Jing; Jin, Han; et al. (Oncotarget, 2016)
The lack of information concerning individual variation in drug-metabolizing enzymes is one of the most important obstacles for designing personalized medicine approaches for hepatocellular carcinoma (HCC) patients. To assess cytochrome P450 (CYP) in the metabolism of endogenous and exogenous molecules in an HCC setting, the activity changes of 10 major CYPs in microsomes from 105 normal and 102 HCC liver tissue samples were investigated. We found that CYP activity values expressed as intrinsic clearance (CLint) differed between HCC patients and control subjects. HCC patient samples showed increased CLint for CYP2C9, CYP2D6, and CYP2E1 compared to controls. Meanwhile, CYP1A2, CYP2C8, and CYP2C19 CLint values decreased and CYP2A6, CYP2B6, and CYP3A4/5 activity was unchanged relative to controls. For patients with HCC accompanied by fibrosis or cirrhosis, the same activity changes were seen for the CYP isoforms, except for CYP2D6 which had higher values in HCC patients with cirrhosis. Moreover, CYP2D6*10 (100C>T), CYP2C9*3 (42614 A>C), and CYP3A5*3 (6986A>G) polymorphisms had definite effects on enzyme activities. In the HCC group, the CLint of CYP2D6*10 mutant homozygote was decreased by 95% compared to wild-type samples, and the frequency of this homozygote was 2.8-fold lower than the controls.In conclusion, the activities of CYP isoforms were differentially affected in HCC patients. Genetic polymorphisms of some CYP enzymes, especially CYP2D6*10, could affect enzyme activity. CYP2D6*10 allelic frequency was significantly different between HCC patients and control subjects. These findings may be useful for personalizing the clinical treatment of HCC patients as well as predicting the risk of hepatocarcinogenesis.